Peran Celebrity Endorsement Dan Tagline Terhadap Brand Awareness Konsumen N’Pure Di Purwakarta - Kusumadewi, Ade Nurhayati; Marlina, Ropi; Mawardi, Amna; Laela, Ela; Asih, Sheni Mulya (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
This research was conducted to determine the effect of celebrity endorsements and taglines on brand awareness. In this study, data collection was used in the form of a non-probability sampling technique, namely a sampling technique that does not provide repeat or equal opportunity for each member of the population to be sampled. The data analysis method used in this study is multiple linear regression with the help of SPSS 25 software. Based on the results of the research that has been done, it shows that partially celebrity endorsements and taglines have a positive and significant effect on brand awareness. And all the dependent variables have a simultaneous effect on brand awareness with a calculated F value of 35.365 with a significant level of 0.000 <0.05. And the R square value shows a result of 0.429, which means that all dependent variables have a simultaneous effect of 42.9%. Keywords: Celebrity Endorsement, Tagline, Brand Awareness